Data from Low impact of FTC on organic carbon and metals in waters of permafrost peatlands - Payandi-Rolland, D (via Mendeley Data) (2020)
This dataset came from freeze-thaw cycle experiments on diverse dissolved OM origins from permafrost peatlands.